1986
DOI: 10.1073/pnas.83.14.5277
|View full text |Cite
|
Sign up to set email alerts
|

Experimental metastasis in nude mice of NIH 3T3 cells containing various ras genes.

Abstract: These studies have compared the ability of NIH 3T3 cells containing different ras oncogenes to form tumor nodules in the lungs of nude mice after tail vein injection. The genes studied include the normal cellular and bladder tumor ras genes, recombinant viral/cellular ras genes, recombinant yeast/mammalian ras genes, and a constructed gene with yeast RASI sequences significantly modified by deletions and an oncogenic mutation. The results show that NIH 3T3 cells containing these genes readily form lethal tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
49
2

Year Published

1989
1989
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(60 citation statements)
references
References 17 publications
9
49
2
Order By: Relevance
“…Activated Ras, Rac, Rho and Cdc42 in particular have long been recognized as regulators of tumor cell invasion (Hernandez-Alcoceba et al, 2000;Campbell and Der, 2004). Ras expressing NIH 3T3 cells are capable of inducing experimental metastasis in nude mice (Bradley et al, 1986). Similarly, invasion is enhanced in NIH 3T3 fibroblasts transformed by the oncogenes v-sis (PDGFR), v-erb-B (EGFR), v-mos, v-ras and v-fos (Melchiori et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Activated Ras, Rac, Rho and Cdc42 in particular have long been recognized as regulators of tumor cell invasion (Hernandez-Alcoceba et al, 2000;Campbell and Der, 2004). Ras expressing NIH 3T3 cells are capable of inducing experimental metastasis in nude mice (Bradley et al, 1986). Similarly, invasion is enhanced in NIH 3T3 fibroblasts transformed by the oncogenes v-sis (PDGFR), v-erb-B (EGFR), v-mos, v-ras and v-fos (Melchiori et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…One common mutation in the Ha-Ras gene is the EJ mutation, which consists of substitution of valine for glycine in codon 12. Cells carrying this mutation colonize the lungs of athymic nude mice after tail vein injection (Bradley et al, 1986;Zhang and Schultz, 1992). Moreover, it has been demonstrated that both ERK1/2 and JNK are active in Ha-Ras EJ stably transfected NIH3T3 cells, but only ERK was required for an invasive phenotype (Janulis et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…NIH3T3 is a nontransformed cell line and does not form tumors or lung metastasis when injected into nude mice (40). However, stable overexpression of different oncogenes has been known to induce oncogenic transformation of NIH3T3 cells (40).…”
Section: C17orf37 Prenylation Enhances Metastatic Dissemination and Cmentioning
confidence: 99%